PRELIMINARY STUDY OF MEVALONOLACTONE MEASUREMENT USING TLC-DENSITOMETRY METHOD - Balqis Azzahra, Diva
Heterologous expression of the mevalonate pathway in Bacillus subtilis was carried out as an effort to increase the ability to produce terpenoids. A simple and fast quantification method is needed for clone selection. Therefore, a preliminary study was carried out to prove the ability of the thin layer chromatography densitometry (TLC-densitometry) method in calculating mevalonolactone, the lactone form of mevalonate, especially B. subtilis which carries the upper mevalonate pathway. There are two treatments for this B. subtilis strain, with non-induced and induced by Isopropyl ?-D-1-thiogalactopyranoside (IPTG). The resulting mevalonate was derivatized into mevalonolactone at pH 2 and then extracted with the solvent, ethyl acetate. Preliminary studies were carried out according to The International Council for Harmonisation (ICH) guidelines using the mobile phase n-hexane-acetone (2,6:2,4 v/v). This method shows good specificity with resolution >2 and selectivity >1. Linearity was observed in the range 100-600 ng/?l (R2= 0,999). The detection limit and quantification limit were 24,910 ng/?l and 75,485 ng/?l, respectively. The accuracy and precision of this method also meet the requirements. Accuracy was calculated based %recovery (102,237; 99,042; and 100,276%). Meanwhile, intra-day precision was calculated with %RSD values (4,289; 3,786; and 4,375%) and inter-day precision (3,811; 2,643; and 3,398%). After that, mevalonolactone levels were measured from the IPTG-induced samples with a value of 1,002 mg/L culture which was equivalent to mevalonate of 1,141 mg/L culture. Based on the research results, mevalonolactone measurements using the TLC-densitometry method can be carried out if the sample is spiked first because the MVAL level is below the limit of quantification.